Original paperImpact of intra-aortic balloon pump on long-term mortality of unselected patients with ST-segment elevation myocardial infarction complicated by cardiogenic shock - Dziewierz, Artur; Siudak, Zbigniew; Rakowski, Tomasz; Kleczyński, Paweł; Zasada, Wojciech; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction : A large, randomised trial (IABP-SHOCK II) confirmed no benefit of intra-aortic balloon pump (IABP) on clinical outcomes of patients with ST-segment elevation myocardial infarction (STEMI) complicated by cardiogenic shock. However, the ‘sickest’ patients are often excluded from randomised clinical trials, so it is difficult to generalise expected outcomes from randomized clinical trials to the real life setting. Aim: We sought to evaluate the impact of IABP on 1-year mortality of unselected patients with STEMI presenting in cardiogenic shock. Material and methods : Data were gathered for 1,650 consecutive patients with STEMI transferred for primary angioplasty from hospital networks in 7 countries in Europe from November 2005 to January 2007 (the EUROTRANSFER registry population). Of them, 51 patients with cardiogenic shock on admission were identified and stratified based on the use of IABP. Outcome results were adjusted for age and sex, to control possible selection bias. Results: At the discretion of the operators, IABP was applied in 30 patients (58.8%, IABP group). The remaining 21 patients were treated without IABP (no-IABP group). The use of IABP was more frequent among males, younger patients, and patients with STEMI of the anterior wall. There was no difference in 30-day mortality in patients with and without IABP (no-IABP vs. IABP: 38.1% vs. 33.3%; adjusted OR 1.79 (95% CI 0.43–7.52); p = 0.43). Similarly, IABP had no impact on 1-year mortality (42.9% vs. 33.3%; adjusted OR 1.27 (95% CI 0.32–5.09); p = 0.74). One-year mortality was comparable among patients who survived hospitalisation (14.3% vs. 13%; p = 0.64). Conclusions : We observed no benefit of IABP on short – and long-term mortality of unselected patients with STEMI complicated by cardiogenic shock.